DA'WAH STRATEGY OF THE PESANTREN IN CULTIVATING ISLAMIC FASHION STYLE AMONG FEMALE STUDENTS: A Case Study at Sunan Drajat Female Islamic Boarding School, Banjaranyar, Paciran, Lamongan - Ainur Rofiq; Lilik Khusniyah Putri (Indonesian Journal of Islamic Communication, 2023)
In Indonesia, the implementation of da'wah has various examples, one of which is through Islamic boarding schools. One of the strategies of Islamic da'wah is to civilize students in dressing, one of which is the Sunan Drajat female Islamic Boarding School. This study aims to answer several problem formulations: 1) How is the Islamic Boarding School's Da'wah Strategy in Cultivating the Islamic Dress Style of Santri at the Sunan Drajat female Islamic Boarding School? 2) What are the factors that support and hinder the Islamic Boarding School's Da'wah Strategy in Cultivating the Islamic Clothing Style of Santri at the Sunan Drajat female Islamic Boarding School? In this research, the researcher is a qualitative research type, the researcher collects and uses data analysis from interviews, observations and documentation of the Pengurs and Santri at Sunan Drajat female Islamic Boarding School. Dressing etiquette, and the supporting factor of this da'wah strategy is the cooperation of the administrators who make it easier for these activities to take place. In contrast, the inhibiting factor is the lack of communication from the boarding school administrators with the dormitories to report students who violate these regulations. From the results of this study, it is suggested that future researchers can develop other variables that have the effect of increasing da'wah